The art of experiencing: reflective appreciative actor training towards well-being, artistry, and personal agency. Issue 2 (21st June 2022) - Loth, Jo; Neideck, Jeremy
Abstract : This article draws on qualitative data gathered during research workshops exploring embodied learning through the Suzuki Method of Actor Training and Linklater Voice. In it, we propose forms of resistance to neoliberal educational trends by developing actors' well-being and artistry through a methodology of Reflective Appreciative Education. Segmentation and commodification of student skills are part of a global trend in neoliberal education. In opposition to this trend, Bryon (2014 ) advocates for integrative models of actor training. Recent Australian studies have also recommended that actor training addresses psychological well-being in order to redress actors' significantly higher levels of depression, anxiety and perfectionism. Analysis of participant data gathered during our study revealed a shift from what Mather and Hulme (2013 ) describe as a 'Performance Model' to a 'Mastery Model.' Participants also began to value and focus on their experiences within the exercises and draw insight from their own experiences. In addition to developing techniques for mental health and resilience, we found this shift to bring a sense of vulnerability and personal agency to heightened performance forms. This article will describe a working process in which actors' mental health and well-being is developed alongside their artistry through focusing on 'being present' and 'experiencing.'